2015
DOI: 10.1007/s11837-015-1328-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Aspects of Homogeneous Nucleation Enhanced by Icosahedral Short Range Order in Liquid Fcc-Type Alloys

Abstract: We have recently shown that minute solute element additions to liquid metallic alloys can strongly influence the nucleation of the fcc phase and act as a grain refinement method. Electron back-scattered diffraction observations revealed a concomitant increase in the percentage of nearest neighbor (nn) grains that are in a twin relationship. Furthermore, multiple-twinned (MT) nn grain configurations with a fivefold symmetry around a common h110i direction have been identified, an occurrence that can be explaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…1). [11] Based on the observations made on the Al-Zn-Cr system and on theoretical considerations, we then proposed the following nucleation mechanism (see Fig. 2): (i) iQC's form in the liquid from ISRO of atoms in the liquid; (ii) They grow, thus depleting the melt in Cr atoms (the system is peritectic [12] ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1). [11] Based on the observations made on the Al-Zn-Cr system and on theoretical considerations, we then proposed the following nucleation mechanism (see Fig. 2): (i) iQC's form in the liquid from ISRO of atoms in the liquid; (ii) They grow, thus depleting the melt in Cr atoms (the system is peritectic [12] ).…”
mentioning
confidence: 99%
“…In a recent contribution presented at the occasion of this Hume-Rothery symposium, [11] we have suggested, based on thermodynamic considerations, that the iQC-mediated nucleation of the fcc phase could be viewed in a way similar to precipitation of a stable second phase from a supersaturated solid solution (e.g., a sequence of metastable phases such as h'' fi h' fi h Al 2 Cu in Al-Cu or a¢ rhomb fi a¢ fi Zn in Al-Zn alloys). In such phase transformations, the sequence usually starts from soluterich Guinier-Preston (GP) zones which can be viewed as a spinodal decomposition of the parent phase.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneous nucleation on foreign particles such as Al on TiB 2 or TiC particles has been shown to be athermal and thus does not follow standard theories, at least at small undercooling [11]. Finally, it has been shown recently that homogeneous nucleation in the liquid might depend on the short range order of atoms in the liquid, itself influenced by minute additions of solute elements [71].…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that icosahedral quasicrystals (iQC's) can also play a major role in the nucleation of the fcc Al phase during solidification of an Al-20wt%Zn alloy [14,15]. Small additions of Cr (1000 ppm) in the liquid metal drastically decrease the size of the fcc grains and induce an abnormally high fraction of twin or near-twin grain boundaries.…”
Section: Introductionmentioning
confidence: 99%